2007
DOI: 10.1093/jpepsy/jsm044
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Parental Overprotection, Perceived Child Vulnerability, and Parenting Stress to Uncertainty in Youth with Chronic Illness

Abstract: Specific parenting variables are associated with youth-reported illness uncertainty; however, their relationship varies according to developmental level. Although OP has been identified as a predictor of child psychological outcomes in other studies, it does not appear to be associated with illness uncertainty in youth with DM1 or asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
78
2
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 42 publications
9
78
2
3
Order By: Relevance
“…21 Because in the original study no mean scores were reported, published mean scores of another representative study among parents of children with chronic illnesses were used. 12 Internal consistency for the current sample was 0.88.…”
Section: Assessment Instrumentsmentioning
confidence: 81%
See 1 more Smart Citation
“…21 Because in the original study no mean scores were reported, published mean scores of another representative study among parents of children with chronic illnesses were used. 12 Internal consistency for the current sample was 0.88.…”
Section: Assessment Instrumentsmentioning
confidence: 81%
“…10 In a sample of parents of children with cancer, perceived vulnerability predicted child emotional adaptation (that is, anxiety, depression) 11 and in a sample of parents of children with chronic illnesses, perceived vulnerability predicted illness uncertainty. 12 Perceived vulnerability has not yet been studied in parents of SCT survivors.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in a sample of children with spina bifida, Holmbeck and colleagues (2002) found that elevated levels of parental overprotection were significantly related to less autonomy and more externalizing behavior problems in their children. In addition to their behaviors, parental beliefs (e.g., perceived child vulnerability) have been associated with increased levels of illness uncertainty in adolescents with Type I diabetes mellitus (Mullins et al, 2007). In fact, one of the single most reliable predictors of a child's adjustment to a chronic illness is parent adjustment (Mullins & Chaney, 2001).…”
Section: Transactional Stress and Coping Modelmentioning
confidence: 99%
“…It is well documented that IMD present an emotional burden to parents (Cederbaum et al 2001;Packman et al 2007) and that parents who may be struggling to cope potentially create greater anxiety and worry in their children (Mullins et al 2007). In the current study, poorer parent coping was associated with more emotional symptoms in children, and poorer family management was associated with more externalising behaviours such as conduct problems and hyperactivity in children.…”
Section: Discussionmentioning
confidence: 99%